Rediseño del filtro de mangas del área de premezclados para la Planta CEMEX Costa Rica - Gutiérrez-Brenes, Greivin David (Instituto Tecnológico de Costa Rica, 2017)
CEMEX Costa Rica is one of the biggest companies in the world, with an important social and environmental impacts, which is why it is necessary to comply with the stipulated requirements for responsible and pollutant production. The company is committed with the environment, so are the called "sleeves filters" that are responsible to eliminating impurities from the air for better production and less dust pollution. It should be kept in mind that Costa Rica Ministry of Health must comply with the rules to avoid harm to the environment and the health of people. In the premixing section of the company is where the stone size reduction to produce cement, is carried out, so the amount of dust in the air is greater and therefore must have a particulate collector system for the storage and treatment of dust in the work area. This report proposes a solution to redesign one of the collectors to perform a maximum particles collection and make the process more efficient. This proposal consists of conducting research, measurements and optimal designs to propose a solution. Once the best collection alternative has been selected, the material suitable for the filtration will be selected, as well as the cleaning system required for this application. Also, a projection of the economic cost of the particle collector is made and thus have an investment reference. Finally, maintenance routines are created to maintain the efficiency of the particle collector as high as possible.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Contaminación; Polvo; Piedra Caliza; Normas; Rediseño; Research Subject Categories::TECHNOLOGY::Engineering mechanics